The efficacy of manual joint mobilisation/manipulation in treatment of lateral ankle sprains: a systematic review. Issue 5 (26th August 2013) - Loudon, Janice K; Reiman, Michael P; Sylvain, Jonathan
Abstract : Background: Lateral ankle sprains are common and can have detrimental consequences to the athlete. Joint mobilisation/manipulation may limit these outcomes. Objective: Systematically summarise the effectiveness of manual joint techniques in treatment of lateral ankle sprains. Methods: This review employed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. A computer-assisted literature search of MEDLINE, CINHAL, EMBASE, OVID and Physiotherapy Evidence Database (PEDro) (January 1966 to March 2013) was used with the following keywords alone and in combination 'ankle', 'sprain', 'injuries', 'lateral', 'manual therapy', and 'joint mobilisation'. The methodological quality of individual studies was assessed using the PEDro scale. Results: After screening of titles, abstracts and full articles, eight articles were kept for examination. Three articles achieved a score of 10 of 11 total points; one achieved a score of 9; two articles scored 8; one article scored a 7 and the remaining article scored a 5. Three articles examined joint techniques for acute sprains and the remainder examined subacute/chronic ankle sprains. Outcome measures included were pain level, ankle range of motion, swelling, functional score, stabilometry and gait parameters. The majority of the articles only assessed these outcome measures immediately after treatment. No detrimental effects from the joint techniques were revealed in any of the studies reviewed. Conclusions: For acute ankle sprains, manual joint mobilisation diminished pain and increased dorsiflexion range of motion. For treatment of subacute/chronic lateral ankle sprains, these techniques improved ankle range-of-motion, decreased pain and improved function.